THE EFFECT OF MARKETING MIX ON CONSUMER SATISFACTION AND ITS IMPACT ON “ROTI MAROS” CONSUMER LOYALTY IN MAROS DISTRICT - Hairil Nurdin; Jusni Jusni; Jumidah Maming (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2020)
Considering the rapid competition of the world economy at this time, so the government must really pay attention to policies, climate change, and renewal of the economy, and participate in making economic policies that have a positive impact in the future. One of the micro businesses as a buffer for the national economy is the food industry which has a very large market demand. The purpose of this study was to determine the effect of marketing mix (price, product, promotion, place) on consumer satisfaction Maros bread, to determine the effect of marketing mix on customer loyalty, to determine the effect of customer satisfaction on customer loyalty, and to determine the effect of marketing mix on loyalty consumers through consumer satisfaction Roti Maros in Maros Regency. The sample used is all consumers who buy Maros bread in Kab. Maros numbering as many as 80 people. Data collection techniques through observation, interviews, documentation and questionnaires. The analysis technique uses validity test, reliability test, descriptive analysis, path analysis, hypothesis testing and sobel test analysis. The results found that the marketing mix had a positive and significant effect on customer satisfaction of Roti Maros. The marketing mix has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty Roti Maros. The marketing mix has a positive and significant effect on the customer loyalty of Roti Maros if mediated by customer satisfaction.